Microeconomic Determinants of Domestic Tourism Expenditure in India - Mehtabul Azam (Institute of Labor Economics (IZA), 2022)
Using a nationally representative household survey from India, we examine individuals' domestic tourism participation and trip expenditure decisions together. We control for a large set of explanatory variables broadly classified as economic, socio-demographic and trip related characteristics. We use two-part (hurdle) model to allow explanatory variables to have differential affects on each decision. We find that education is an important determinant for both the decisions. Moreover, trip-related characteristics (party size, stay length, ac- commodation type, travel mode, and destination) are also important determinants of trip expenditure in addition to economic and socio-demographic characteristics. The unconditional quantile regression results show the heterogeneity in the impact of many variables across the trip expenditure distribution. The differences in trip expenditure across age-groups are primarily in the upper half of the trip expenditure distribution. A trip arranged under a tour package leads to an increase in trip expenditure at the higher quantiles of trip expenditure distribution.
Keywords: Z3; O12; 330; unconditional quantile regression; two-part model; expenditure; tourism participation